Suppression of AGR2 in a TGF-β-induced Smad regulatory pathway mediates epithelial-mesenchymal transition - Sommerova, Lucia; Ondrouskova, Eva; Vojtesek, Borivoj; Hrstka, Roman (BMC cancer, 2017)
BACKGROUND: During cancer progression, epithelial cancer cells can be reprogrammed into mesenchymal-like cells with increased migratory potential through the process of epithelial-mesenchymal transition (EMT), representing an essential step of tumor progression towards metastatic state. AGR2 protein was shown to regulate several cancer-associated processes including cellular proliferation, survival and drug resistance. METHODS: The expression of AGR2 was analyzed in cancer cell lines exposed to TGF-β alone or to combined treatment with TGF-β and the Erk1/2 inhibitor PD98059 or the TGF-β receptor specific inhibitor SB431542. The impact of AGR2 silencing by specific siRNAs or CRISPR/Cas9 technology on EMT was investigated by western blot analysis, quantitative PCR, immunofluorescence analysis, real-time invasion assay and adhesion assay. RESULTS: Induction of EMT was associated with decreased AGR2 along with changes in cellular morphology, actin reorganization, inhibition of E-cadherin and induction of the mesenchymal markers vimentin and N-cadherin in various cancer cell lines. Conversely, induction of AGR2 caused reversion of the mesenchymal phenotype back to the epithelial phenotype and re-acquisition of epithelial markers. Activated Smad and Erk signaling cascades were identified as mutually complementary pathways responsible for TGF-β-mediated inhibition of AGR2. CONCLUSION: Taken together our results highlight a crucial role for AGR2 in maintaining the epithelial phenotype by preventing the activation of key factors involved in the process of EMT.
Keywords: Vimentin; onkogenní proteiny; mukoproteiny; E-cadherin; epitelo-mezenchymální tranzice; regulace genové exprese u nádorů; genový knockdown; kadheriny; buněčná adheze; Cell Movement; Humans; Metastasis; Cadherins; Transforming Growth Factor beta; Oncogene Proteins; Cell Adhesion; EMT; Smad Proteins; Cell Line, Tumor; Epithelial-Mesenchymal Transition; nádorové buněčné linie; Proteins; TGF-β; proteiny; transformující růstový faktor beta; Gene Expression Regulation, Neoplastic; Mucoproteins; proteiny Smad; Gene Knockdown Techniques; pohyb buněk; lidé; Signal Transduction; AGR2; vimentin; signální transdukce